The CoRoT‐GES Collaboration: Improving red giants spectroscopic surface gravitity and abundances with asteroseismology. Issue 8 (30th September 2016) - Valentini, M.; Chiappini, C.; Miglio, A.; Montalbán, J.; Rodrigues, T.; Mosser, B.; Anders, F.; CoRoT RG Group,; GES Consortium,
Abstract: Nowadays large spectroscopic surveys, like the Gaia‐ESO Survey (GES), provide unique stellar databases for better investigating the formation and evolution of our Galaxy. Great attention must be paid to the accuracy of the basic stellar properties derived: large uncertainties in stellar parameters lead to large uncertainties in abundances, distances and ages. Asteroseismology has a key role in this context: when seismic information is combined with information derived from spectroscopic analysis, highly precise constraints on distances, masses, extinction and ages of red giants can be obtained. In the light of this promising joint action, we started the CoRoT‐GES collaboration. We present a set of 1111 CoRoT stars, observed by GES from December 2011 to July 2014, these stars belong to the CoRoT field LRc01, pointing at the inner Galactic disk. Among these stars, 534 have reliable global seismic parameters. By combining seismic informations and spectroscopy, we derived precise stellar parameters, ages, kinematic and orbital parameters and detailed element abundances for this sample of stars. We also show that, thanks to asteroseismology, we are able to obtain a higher precision than what can be achieved by the standard spectroscopic means. This sample of CoRoT red giants, spanning Galactocentric distances from 5 to 8 kpc and a wide age interval (1–13 Gyr), provides us a representative sample for the inner disk population.